A review of the effects of Sarbanes-Oxley on stock price - Daniel Boylan (Global Business & Finance Review (GBFR), 2015)
The Sarbanes-Oxley Act (SOX) has been in place for over a decade, and the effects of the legislation are widely debated in the business community. The problem to be investigated is the impact of the Act on the disclosure of financial information and the strength of the internal controls a company has in place to determine whether SOX has affected publicly traded companies in the United States. SOX resulted in the creation of the Public Company Accounting Oversight Board and provides for the establishment of audit reporting standards and the investigation, inspection, and enforcement of public accounting firms. The Act has decreased the number of discretionary accruals, addressed the backdating of stock options, addressed material reporting weaknesses, and increased the quality of internal controls. Several significant factors support the assertion that the benefits of SOX outweigh the compliance costs of its implementation.
Keywords: 650; Sarbanes-Oxley; SOX; Stock Price